Effects of temperature and land-use change on soil organic matter dynamics in a permafrost-affected ecosystem ... - Peplau, Tino Andreas (Hannover : Institutionelles Repositorium der Leibniz Universität Hannover, 2023)
Subarctic ecosystems are among the regions on earth that experience the strongest impact by climate change. As a result of global warming, agricultural centers are shifting poleward into previously non-viable regions of subarctic forests. These subarctic ecosystems are among those predicted to be most strongly impacted by rising global temperatures. Additionally, because agriculture north of 60 degrees latitude has been historically limited, there are few studies which systematically examine the effect of converting subarctic forests for cropland or grassland use on soil carbon. The aim of this thesis was to quantify the effects of land-use change from boreal forest to cropland and grassland on the stocks and composition soil organic carbon. Therefore, three studies were conducted in the Canadian Yukon Territory. First, the effect of soil warming on stocks and fractions of the soil organic matter was quantified by using proximity to a geothermal spring in a subarctic ecosystem as a long-term warming ... : Subarktische Ökosysteme gehören zu den am stärksten vom Klimawandel betroffenen Region der Erde. Im Zuge der Erderwärmung lässt sich eine Verlagerung der landwirtschaftlichen Zentren in Richtung der Pole beobachten, die zu einer Ausbreitung der Landwirtschaft hinein in subarktische Waldregionen führt. Da Landwirtschaft in Regionen nördlich von 60°N bislang nur eine untergeordnete Rolle spielte, existieren kaum Studien, die den Effekt des Landnutzungswandel von Wald zu Acker und Wald zu Grünland auf den Bodenkohlenstoff systematisch erfasst haben. Ziel der Dissertation war es, die Auswirkungen des Landnutzungswandels von borealem Wald zu Acker und Grünland auf die Vorräte und die Zusammensetzung der organischen Bodensubstanz zu quantifizieren. Den Kern der Dissertation bilden drei Studien, die im kanadischen Yukon Territory durchgeführt wurden. Zunächst wurde der Effekt von Bodenerwärmung auf die Vorräte und Fraktionen der organischen Bodensubstanz quantifiziert, in dem eine geothermale Quelle als ...